Pendidikan Karakter Siswa Ditinjau Dari Implementasi Pendidikan Agama Islam Di SMK Genius Bandung - Fery Farnian Syarif; Kun Nurachadijat (Simpati, 2023)
Measurable character education can have an effect on students to grow into better individuals, resulting from constructive feedback through the teacher's exemplary. As a motivator the teacher can move students with their own awareness and responsibility so that they are willing to learn. Islamic education must be able to move the character of students according to the example of Rasulullah SAW. Islam, especially Islamic education, is seen as a binder and guide to the true path, so that the culture that arises will be able to provide benefits, not only to himself, but also to others. To find out the implementation of Islamic education on students' character building, this research uses a qualitative approach. The research method used is a case study using in-depth interviews with school principals, Islamic education teachers and several students of SMK Genius Bandung. Direct observation and document analysis as data collection techniques, triangulation of sources and methods are used to test the authenticity of the data obtained. The result of this study shows that Islamic education is not only limited to academic assessment, spiritual development, understanding of moral values, and adherence to Islamic principles, in addition it is also important to consider aspects of students' attitudes, morals, and behavior towards each other and their environment which is in accordance with the goals of student character education. Based on the research it is concluded that Islamic education as an independent research variable has a very strong positive relationship with the students' character building that means it has a very large influence on the students' character building. Therefore, a holistic and integrated evaluation will provide a clear picture that is more comprehensive about Islamic education in the students' character building at SMK Genius Bandung.